2021
DOI: 10.1111/1748-8583.12423
|View full text |Cite
|
Sign up to set email alerts
|

Does international work experience pay off? The relationship between international work experience, employability and career success: A 30‐country, multi‐industry study

Abstract: Drawing on human capital theory, our study examines the relationship between international work experience and individuals' career success in terms of promotions and subjective financial success. We propose that these relationships are mediated by external employability and hypothesise a moderating role of national‐level economic freedom. Using data from 19,421 respondents, residing in 30 countries and working in different occupational groups (managers, professionals, clerical and blue‐collar workers), our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…The study conducted by Qenani, MacDougall & Sexton (2014), for instance, discovered that those students who gained work experience through internships or other relevant work placements programmes were likely to possess employability traits. Correspondingly, a study that unpacked the value of international work experience found that work experience is correlated with improved employability prospects, professional development, and career success (Andresen et al, 2021). While the internship provider's perspective indicated the important role of the internship in developing employability skills, some interns were found to lack work readiness owing to the lack of problem solving and communication skills among others (Jackling & Natoli, 2015).…”
Section: Graduate Work Experience Programmes and Employabilitymentioning
confidence: 99%
“…The study conducted by Qenani, MacDougall & Sexton (2014), for instance, discovered that those students who gained work experience through internships or other relevant work placements programmes were likely to possess employability traits. Correspondingly, a study that unpacked the value of international work experience found that work experience is correlated with improved employability prospects, professional development, and career success (Andresen et al, 2021). While the internship provider's perspective indicated the important role of the internship in developing employability skills, some interns were found to lack work readiness owing to the lack of problem solving and communication skills among others (Jackling & Natoli, 2015).…”
Section: Graduate Work Experience Programmes and Employabilitymentioning
confidence: 99%
“…(1) Different disciplines focus on divergent definitions and separate groups of internationally mobile individuals, leading to disjunction in the organizational and political understanding of issues related to individual mobility. For example, management studies address 'expatriation', which is often considered to have positive effects on the careers of organizationally assigned expatriates (Andresen et al, 2022). In turn, 'migration' is used in economics, sociology, and politics, and it suggests potential employment challenges and career breaks for migrants (Visintin et al, 2015).…”
Section: Originality and Innovative Aspects Of The Glomo Projectmentioning
confidence: 99%
“…Thus, an international relocation involves a need to adjust expatriate thought patterns and scripts to effectively interact with people and adapt to situational demands across cultures (Shaffer et al, 2012). Expatriates also often have demanding jobs with a high level of autonomy and thus, expatriation often has an extensive impact on individuals' careers (Andresen et al, 2022;Mello et al, 2022). One of the frameworks that is used to understand the development that takes place abroad is the career capital framework (Sullivan & Arthur, 2006).…”
Section: Part Ii: Expatriates' Career Paths Capital and Sucessmentioning
confidence: 99%
“…As expatriation is such a developmental experience it may also have extensive career impacts. The existing evidence on the impact of expatriation on careers is still quite limited and findings are controverse, thus more research has been called for regarding both subjective and objective career success (Andresen et al, 2022;Suutari et al, 2018) of both repatriates (Chiang et al, 2018) and re-expatriates who continue their international careers (Ho et al, 2016). Furthermore, we have far less evidence on careers of SIEs than of AEs (Mello et al, 2022).…”
Section: Part Ii: Expatriates' Career Paths Capital and Sucessmentioning
confidence: 99%